Effect of margin eligibility on stocks listed on Stock Exchange of Singapore. - Chan, Hui Ling. (2008)
This study examines the effect of margin eligibility of stocks that are listed on the Stock Exchange of Singapore. It seeks to investigate the impact of a change in margin eligibility on abnormal returns, return volatility levels and the trading activity of stocks that become marginable and/or non-marginable. The analysis also test for firm size effect. The study is being carried out over a six-year period from 1993 to 1998, during which four changes were made to the list of marginable stocks.